Cytokine levels are modulated after acute exercise performance in hypoxia - Lira, F. S.; Machado, P. P.; Santos, S. A.; Silva, E. T.; Caris, A.; Oller do Nascimento, C. M.; Oyama, L. M.; Tufik, S.; Santos, R. V. T.; de Mello, M. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Cytokine, maily interleukin 6 (IL-6), interleukin 10 (IL-10), and interleukin 1 receptor antagonist (IL-1ra) play a key role in the immune system and metabolism during periods of stress and rest. It known that, during and after exercise cytokine levels are modulated. However, the concentration of these cytokines during and after exercise in the hypoxia exposure is unknown. Our hypothesis is that exercise performance in the hypoxia exposure may impair cytokine levels. Methods: Eight male subjects were exposed to normobaric hypoxic exposure at 4,200 m or sea level and performance treadmill exercise for 1 hour (~ 50% VO2peak). Plasma levels of cytokine (IL-6, TNF-alpha, IL-10 and IL-1ra) were determined at rest, and immediately and 1 h after exercise bouts. Results: No differences were found in performance parameters (heart ratio, oxymetric, rating of perceived exertion). IL-6 levels was increased immediately and 1 hour after exercise than rest in both altitudes (p<0.001). Interestly, increased levels of TNF-alpha and IL-10 immediately after exercise, as compared as rest and 1 hour after exercise, were observed only in the sea level (p<0.05). We also found that, IL-1ra levels was increased 1 hour after exercise in relation to rest and immediately after exercise in both altitudes (p<0.05). Discussion: The inflammatory markers increased in serum, skeletal muscle and adipose tissue following exhaustive exercise is well-established (Petersen and Pedersen 2005, Rosa et al 2011). There is no data in the literature about the effect of the performance exercise in hypoxic exposure at 4,200 m upon cytokine levels. Our exercise sea level data are according with the literature, showing that cytokine levels are increased after acute exercise. However, the usual condition is impairing when exercise is performance in hypoxic exposure at 4,200 m. These alterations may, at least in part, contribute to the immunosuppression state. These findings can help to better knowing upon effects the hypoxic exercise regimen on immune system response.